Abrupt changes in Indian summer monsoon strength during 33, 800 to 5500 years B.P. Issue 13 (7th July 2015) - Dutt, Som; Gupta, Anil K.; Clemens, Steven C.; Cheng, Hai; Singh, Raj K.; Kathayat, Gayatri; Edwards, R. Lawrence
Abstract Speleothem proxy records from northeastern (NE) India reflect seasonal changes in Indian summer monsoon strength as well as moisture source and transport paths. We have analyzed a new speleothem record from Mawmluh Cave, Meghalaya, India, in order to better understand these processes. The data show a strong wet phase 33, 500–32, 500 years B.P. followed by a weak/dry phase from 26, 000 to 23, 500 years B.P. and a very weak phase from 17, 000 to 15, 000 years B.P. The record suggests abrupt increase in strength during the Bølling‐Allerød and early Holocene periods and pronounced weakening during the Heinrich and Younger Dryas cold events. We infer that these changes in monsoon strength are driven by changes in temperature gradients which drive changes in winds and moisture transport into northeast India.